2011
DOI: 10.5152/akd.2011.190
|View full text |Cite
|
Sign up to set email alerts
|

Increased neopterin levels and its association with angiographic variables in patients with slow coronary flow: an observational study

Abstract: Objective: Although various inflammatory markers have been studied in patients with slow coronary flow (SCF), serum neopterin levels have not been studied previously. We investigated the serum neopterin and high sensitivity C-reactive protein (hs-CRP) levels and the relationship between neopterin and hs-CRP levels and TIMI flow in patients with SCF. Methods: The study group consisted of 51 patients with SCF. An age and gender matched control group was composed of 40 subjects. Coronary flow rates of all patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…It is known that neopterin level predicts adverse prognosis in coronary artery disease (34). Elevated serum level of neopterin as a systemic marker of IFN-γ was shown in SCF patients by Varol et al (35). …”
Section: Discussionmentioning
confidence: 92%
“…It is known that neopterin level predicts adverse prognosis in coronary artery disease (34). Elevated serum level of neopterin as a systemic marker of IFN-γ was shown in SCF patients by Varol et al (35). …”
Section: Discussionmentioning
confidence: 92%
“…Besides that, inflammation has been shown to be involved in the development of CSFP [11]. Thus, inflammatory biomarkers have been extensively employed to investigate CSF [12][13][14]. Moreover, Li et al discovered that plasma CRP and interleukin 6 levels were considerably elevated in individuals with CSFP in a recent study [15].…”
Section: Discussionmentioning
confidence: 99%
“…Li et al found that plasma levels of inflammatory factors, hs-CRP and IL-6 in patients with SCF were significantly higher than those of control subjects [23]. Varol et al found higher levels of neopterin, which is thought to be a marker of immune activation and macrophage activity, in the CSF group than the normal coronary flow group [24]. Selçuk et al reported that serum concentrations of adiponectin, a modulator of the inflammatory response in the vascular wall, were decreased in patients with SCF and inversely correlated with mean TIMI frame count [25].…”
Section: Discussionmentioning
confidence: 99%